Optimasi Pembuatan Pellet Rumput Gajah (Pennisetum purpurium) untuk Pakan Ternak Ruminansia - Wisnaningsih User; Suraya Kaffi Syahpura (Inovasi Pembangunan : Jurnal Kelitbangan, 2016)
Pellet is a form of feed material is compacted in such a way from concentrate or forage material in order to reduce the feed properties. The advantage of feed form of pellets is increasing consumption and feed efficiency, increase levels of metabolizable energy of feed, kill pathogens, to extend the storage time, ensure a balance of nutrients feed and preventoxidation of the vitamin, reducing storage space, reduce the cost of transportation, ease of handling and presentation of fee, a high density will increase feed intake and reduced feed scattered, preventing the de-mixin that decomposition back components of the pellet so that the feed consumption in accordance with the standard requirements. This study aims to manufacture pellets elephant grass (Pennisetum purpurium) for ruminant feed in order to obtain effectiveness and high performance and as export opportunities to increase foreign exchange and increase farmers income by utilizing grass degraded land and land less productive. The treatment used is the drying sun and oven, a method of blanching and steam with duration of 5, 10, and 15 minutes early in the process and conditioning treatment water content of 5%, 10%, and 20% of the weight of the material. Making pellets elephant grass (Pennisetum purpureum) with a treatment of drying sun by the method of steam at a temperature of 100 ºC with a duration of 5 minutes can make the nutrient content of elephant grass is a crude fiber 36.5%, crude protein 10.5%, energy metabolism of 4,826 kcal / kg, crude lipid 1.8%, the water content of 85.8%, 2.8% ether extract. ash content 12.5%, 1.5% calcium and 0.4% phosphorus. while the value of Pellet durability index (PDI) of 100% in the can at treatment use water content of 10%.